h+-27=54

Simple and best practice solution for h+-27=54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h+-27=54 equation:



h+-27=54
We move all terms to the left:
h+-27-(54)=0
determiningTheFunctionDomain h-27-54+=0
We add all the numbers together, and all the variables
h=0

See similar equations:

| 9t+1/8=t+6/16+t-4/16 | | 0=-2x-28 | | 3x-2.7=-0.9x-2.18 | | 53=s-2 | | 0.1x+0.001=1/100(x+10) | | 5x+2=6x+0 | | X-3/3x+1=x+4/x | | 1/4p³-1/2p²=20 | | 5x+8=4+7x | | 1.3x-2.7=0.9x-2.18 | | .12t+2=1.2^(t/3) | | (x+18)-(x+15)+(22)=x+28 | | C(441.00)=18n+45 | | 2(1x+2)=12 | | 4x/7+1-1.4=3.6 | | 8a=12=44 | | 9x=3+-24 | | B=5/4(j-25) | | 4n+2=6(1/3n-2=3) | | 2.3+10m=6.58 | | C(445)=18n+45 | | C($445)=18n+45 | | 4=j/8 | | 4.8+10m=8.65 | | -2x÷3=11 | | 11x-7x-7+11=36 | | z=25 | | (3x+-8)(x-6)=0 | | 4x+0.8=28.8 | | 3+27=-5(3x-6) | | -11a=154 | | (3x+8)(x-6)=0 |

Equations solver categories